Application of Spiritual Intelligence-Based Curriculum: A Case Study of Boarding School MAN 2 Kudus - Saliyo Saliyo; Adri Efferi; Saefudin Saefudin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to describe the impact of implementing a spiritual intelligence-based curriculum at the Boarding School